The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1186/s12891-022-05456-w
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of surgical hip dislocation combined with bone graft for adolescents and younger adults with osteonecrosis of the femoral head: a case series and literature review

Abstract: Background Osteonecrosis of the femoral head (ONFH) may occur in the adolescent and younger adults (AYAs). Total hip arthroplasty (THA) is not the best treatment option for younger patients. Surgical hip dislocation (SHD) combined with bone graft can be used in patients at different stages to reconstruct the bone structure in the head and delay the replacement time. The purpose of this study was to evaluate the effect and potential influencing factors of this surgery for ONFH in AYA patients.  … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…However, the limited lifespan of the prosthesis and the increasingly prominent complications make it inevitable for young and middle-aged patients to face revision [16].Therefore, how to improve the success rate of hip preservation treatment is still an important issue in the development of clinical research in ONFH. [3] In 2001, Ganz et al [9] rst proposed the SHD technique, which is designed based on the fact that the main blood supply of the femoral head comes from the deep branch of the rotator medial femoral artery, and it can avoid damage to the blood ow of the femoral head [18].Later on, with the extensive use of IBG in hip preservation surgery, SHD-IBG also came into being which was used in the hip preservation treatment of ARCO stage II and III ONFH [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the limited lifespan of the prosthesis and the increasingly prominent complications make it inevitable for young and middle-aged patients to face revision [16].Therefore, how to improve the success rate of hip preservation treatment is still an important issue in the development of clinical research in ONFH. [3] In 2001, Ganz et al [9] rst proposed the SHD technique, which is designed based on the fact that the main blood supply of the femoral head comes from the deep branch of the rotator medial femoral artery, and it can avoid damage to the blood ow of the femoral head [18].Later on, with the extensive use of IBG in hip preservation surgery, SHD-IBG also came into being which was used in the hip preservation treatment of ARCO stage II and III ONFH [5].…”
Section: Discussionmentioning
confidence: 99%
“…Whether the rate of hip preservation by IBG and PVIBGT is related to the progression of the patient's necrosis of the femoral head degree needs to be further studied. 5 Shortcomings and Prospects the present study, we compared the effectiveness of SHD-IBG and PVIBGT in the treatment of ARCO stage II and III femoral head necrosis at 1 year postoperatively. And through the mid-to-long-term followup of SHD-IBG for 2.5-11 (an average of 77 months) years, combined with a comprehensive analysis of patients with hip preservation failures in the two groups, it can be demonstrated that the two operation methods signi cantly improved patients' Harris scores, but were less effective in ARCO stage II and III femoral head necrosis with extensive involvement of the lateral column.…”
Section: Analysis and Summary Of Reasons For Hip Preservation Failurementioning
confidence: 99%